Assessment of the Temporal and Spatial Variation of the Mercury Content of Lake Nokoué in Southern Benin Republic (West Africa) - Julien G. Adounkpe; N. B. Nadia Azon; Hermione W. Dégila; Peace Hounkpe; Robertson Amoussou (The Scientific World Journal)
Anthropogenic input of mercury into watersheds is becoming increasingly noticeable and is the cause of fishery products contamination. This had led to the Convention of Minamata signed and ratified by the vast majority of the countries in the world. Lake Nokoué in Benin Republic, the most fishery products provider in West Africa, is subject to mercury pollution. The health threat to both the benthic and the consumers of the fishery products from this lake has to be anticipated by precisely determining the dynamics of mercury contamination of the waters and sediments of Lake Nokoué, taking into account the anthropogenic contribution. Water and sediment samples were collected on 23 sites twice a month for four sampling campaigns. Parameters such as pH, salinity, COD, and SS are evaluated in the water. The assessment of total mercury is conducted by cold vapor atomic absorption according to the US EPA 7473 method, using a direct mercury analyzer (DMA-80). On average, the mercury content in Lake Nokoué water is 0.43 ± 0.57 μg/kg. Its variation is linked not only to the seasonal variation but also to that of the suspended matter. South of the lake, the sediments are extremely polluted (5 ≤ Igeo) and present a risk of frequent effects for the benthic species present.